Newcomers in Maribor in the first half of the eighteenth century in the marriage records of the Parish of St. John the Baptist - Hazemali, David (Acta Histriae, 2025)
This article examines the role of newcomers in Maribor during the early eighteenth century through an analysis of 401 marriages recorded between 1700 and 1748 in the Parish of St John the Baptist. At least one spouse in each of these documented marriages originated from outside Maribor (including ar-rivals from German-speaking Styria, from Carinthia and Carniola, as well as nearby towns and villages). The study shows strong evidence that in-migration via marriage was vital for Maribor’s demographic and economic recovery after the late seventeenth-century plague. Newcomers often married into established local families, particularly those of guild masters and artisans, swiftly obtaining burgher status and guild membership. Marriage functioned as a key integration mechanism that transformed ‘outsiders’ into ‘insiders’ and helped replenish skilled labour in the town. The findings highlight that Maribor depended on a constant influx of migrants to sustain its population and craft industries, as was typical of many pre-industrial towns where deaths outpaced births. Through quantitative analysis of marriage registers and illustrative case studies, the article contributes new insights into early modern urban mobility, showing how socially sanctioned institutions like marriage facilitated the integration of migrants into urban society.
Keywords: early-modern urban demography; Maribor; marriage as an integration mechanism; migracije; migrations; newcomers; poroka kot integracijski mehanizem; prišleki; Styria; Štajerska; zgodnjenovoveška urbana demografija